Complex calculations: ethical issues in involving at-risk healthy individuals in dementia research. Issue 9 (31st July 2010) - Pierce, Robin
Abstract : In dementia research evidence is mounting that therapeutic strategies that target moderate and even mild Alzheimer's disease may be missing the 'therapeutic window'. Given that the neuropathology that leads to Alzheimer's disease probably begins somewhere between 10 and 15 years before symptoms manifest, many believe that the optimal therapeutic strategy would target persons in the earliest phases of disease development or even earlier. This would include, for example, persons with prodromal Alzheimer's and even persons who are deemed at risk. Given the nature of research involving the central nervous system, it is conceivable that some therapeutic investigations may involve an increase over minimal risk. This paper examines how, in dementia research, at-risk persons, although healthy, bring multiple and intersecting vulnerabilities to the prospect of research participation even though they are clinically healthy. Current guidelines for research ethics may not provide adequately for the nuances of 'healthy individuals' and their possible vulnerabilities. In the context of neurodegenerative disease, the fact of being 'at risk' alters the vulnerability profile in significant ways. While healthy persons who are at risk of developing dementia may not appear to warrant placement in the research category of vulnerable participants (alongside prisoners, pregnant women and children) careful regard for the vulnerabilities that arise as a result of the intersecting circumstances of being healthy and at risk of an incurable disease are worthy of increased attention and consideration, particularly as the research effort for the increasingly prevalent disease of Alzheimer's moves forward.